2018
DOI: 10.21037/jtd.2018.07.47
|View full text |Cite
|
Sign up to set email alerts
|

Application of albumin/globulin ratio in elderly patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: Background: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) has become an important disease of hospitalized elderly patients, which lack simple and inexpensive indicators for evaluating the condition and prognosis. This study was performed to investigate the clinical significance of the serum albumin/globulin ratio (AGR) in elderly patients with AECOPD.Methods: The data of 252 hospitalized elderly patients with AECOPD, 89 stable COPD patients and 115 elderly healthy individuals were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…5 It can be regarded as an index for predicting the prognosis of AECOPD and other inflammatory diseases. 6 Recent studies indicated that a low AGR may respect a susceptible state to infection. 5,6 We suggested that "re-positive" patients may not sufficiently apparent the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 It can be regarded as an index for predicting the prognosis of AECOPD and other inflammatory diseases. 6 Recent studies indicated that a low AGR may respect a susceptible state to infection. 5,6 We suggested that "re-positive" patients may not sufficiently apparent the virus.…”
mentioning
confidence: 99%
“… 6 Recent studies indicated that a low AGR may respect a susceptible state to infection. 5 , 6 We suggested that “re-positive” patients may not sufficiently apparent the virus. Our results indicated that AGR may potentially have a predictive effect in “re-positive” discharged COVID-19 patients.…”
mentioning
confidence: 99%
“…Changes in serum globulins are thought to be indicative of inflammation and/or host immune response [ 76 ]. A study in the literature found that both CVD-related and independent mortality was high in chronic kidney disease patients with low AGR [ 26 ]. It has been stated in different studies that AGR can be used in the prognostic evaluation of tumors such as HCC, ureteral carcinoma, ovarian and gastric cancer [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the albumin/globulin ratio (AGR) is associated with mortality in chronic obstructive pulmonary disease and chronic renal failure [ 26 , 27 ].…”
mentioning
confidence: 99%
“…Also, especially after Enterobacteriaceae infection, the expression of ALB mRNA in patients is inhibited, and hypoproteinemia is prone to occur. Hypoproteinemia will weaken respiratory defenses and immune function, making patients with TBI more vulnerable to pathogenic microorganisms, viruses, and various inflammatory cells (19). The invasion of a large number of bacteria can aggravate lung infections, promote alveolar exudation, increase secretions, block alveoli, and induce atelectasis.…”
Section: Discussionmentioning
confidence: 99%